The Sacred, the Cursed, the Forgotten… - Piotrowski, Robert (Literatura Ludowa. Journal of Folklore and Popular Culture, 2025)
Review of: Łukasz Miechowicz, Święte i przeklęte. Kamienie w religijności ludowej. Katalog. Wydawnictwo Instytutu Archeologii i Etnologii Polskiej Akademii Nauk, Warszawa 2023.